2006
DOI: 10.1155/2007/915432
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Nutritional Parameters for the Production of Protease from Aspergillus Oryzae

Abstract: Production of protease enzyme by fungus Aspergillus oryzae was investigated. The proteolytic activity was observed when the fungus was grown in the medium containing glucose, malt extract, yeast extract, peptone, K 2 HPO 4 , MgSO 4 and FeSO 4 . The present paper describes the screening of media components and fermentation conditions in shake flask. The organism utilized carbon sources glucose, fructose, sucrose, lactose, dextrin and starch among them glucose was found to be the best carbon source, for nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 7 publications
2
16
0
1
Order By: Relevance
“…Our report is in accordance with Srinubabu et al (2007) who also reported di-ammonium hydrogen orthophosphate for protease production by A. oryzae, whereas, Johnvesly and Naik (2001) observed nitrates as best nitrogen sources.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our report is in accordance with Srinubabu et al (2007) who also reported di-ammonium hydrogen orthophosphate for protease production by A. oryzae, whereas, Johnvesly and Naik (2001) observed nitrates as best nitrogen sources.…”
Section: Discussionsupporting
confidence: 92%
“…Glucose has been universally suggested as the best carbon source (Mehrotra et al, 1999, Srinubabu et al, 2007 as it can be easily metabolized by the microorganisms (Ashour et al, 1996). Adequate amount of enzyme (2054 U/gss) was produced by the isolated strain with glucose, however, sorbitol was found to be best source and maximum yield of enzyme (2531 U/gss) was obtained at a concentration of 200 mg/gss, while the inhibitory effect at higher concentrations might be due to catabolite repression.…”
Section: Discussionmentioning
confidence: 99%
“…As the agitation rate was increased above 120 rpm, the enzyme production decreased. At this speed, aeration of the culture medium was increased which could lead to sufficient supply of dissolved oxygen in the media [17].…”
Section: Effect Of Agitation Rate On Protease Productionmentioning
confidence: 99%
“…Starch concentration decreased along with mold growth as sugar production increased.Aspergillus nigergrowth reached the end of the exponential phase at the 48 th hour. The maximum concentration of sugar achieved was 14.42 g/L.Aspergillus nigeralso consumes fats (Falony et al, 2006) and protein (Srinubabu et al, 2007).If polysaccharide content in the cultivation media is low, residual starch is reduced drastically.…”
Section: Cultivation Of Aspergillus Nigermentioning
confidence: 99%